UX Research practices related to Long-Term UX: a Systematic Literature Review - Martinelli, Suéllen Rodolfo (2024)
Context: The software industry has sought to apply User eXperience (UX) practices that can help maintain a sustainable business. UX practices make it possible to conduct research and make evaluations with users through the application of methods and techniques. But few studies in the literature discuss UX Research practices with Long-Term UX. Objective: The objective of this paper is to identify in the literature what UX Research practices are employed by the software industry and their relationship with Long-Term UX. Methods: We conducted a Systematic Literature Review with string applied in search engines, besides selection criteria and quality assessment applied in the papers. We selected 45 papers that were submitted for the qualitative analysis carried out with coding techniques. Results: 38 UX Research practices were identified and classified between formal and informal practices. We also identified 52 UX methods, techniques, and tools that are used for these UX Research practices. Our findings show that 15 out of 38 practices are related to Long-Term UX. Conclusion: We drew up 14 guidelines for conducting UX Research in the software industry, which includes goals, UX methods, and the means of putting them into practice.